Venomous caterpillars: From inoculation apparatus to venom composition and envenomation. (October 2018) - Villas-Boas, Isadora Maria; Bonfá, Giuliano; Tambourgi, Denise V.
Abstract: Envenomation by the larval or pupal stages of moths occurs when the victim presses their hairs. They penetrate the subcutaneous tissue, releasing toxins such as proteolytic enzymes, histamine and other pro-inflammatory substances. Cutaneous reactions, including severe pain, oedema and erythema are frequent local manifestations of caterpillar envenomation, but, in some cases, the reactions can evolve into vesicles, bullae, erosions, petechiae, superficial skin necrosis and ulcerations. Alternatively, some individual can develop allergic reactions, renal failure, osteochondritis, deformity and immobilization of the affected joints and intracerebral bleeding. Caterpillars produce venom to protect themselves from predators; contact with humans is accidental and deserves close attention. Their venoms have not been well studied, except for toxins from some few species. The present review brings together data on venomous caterpillars of moths, primarily addressing the available literature on diversity among the different families that cause accident in humans, the structures used in their defense, venom composition and clinical aspects of the envenomations. Understanding the molecular mechanisms of action of caterpillars' toxins may lead to the development of more adequate treatments. Highlights: Envenomation by caterpillars of moths occurs when the victim presses their urticating's hairs. Venom apparatus structure varies among the families, but most urticating caterpillars possess hollow hairs or spines containing venom. Caterpillars venoms have not been well studied, except for toxins from few species of Erebidae and Saturniidae families. Envenomation symptoms range from mild events, as cutaneous reactions, to severe events, as intracerebral bleeding.